2008
DOI: 10.3174/ajnr.a1170
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Classic and Atypical Meningiomas with Use of Diffusion Tensor Imaging

Abstract: BACKGROUND AND PURPOSE:The differentiation between classic and atypical meningiomas may have implications in preoperative planning but may not be possible on the basis of conventional MR imaging. Our hypothesis was that classic and atypical meningiomas have different patterns of intratumoral water diffusion that will allow for differentiation between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
6
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 13 publications
5
79
6
4
Order By: Relevance
“…Previous studies investigated the roles of ADC and FA in subtyping meningiomas, but the results were controversial. 7,8,27 In the present study, we found that angiographic vascularity of meningiomas correlated with FA but not with ADC. Whereas ADC measures the average changes of water diffusivity, FA quantifies the diffusion anisotropy.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Previous studies investigated the roles of ADC and FA in subtyping meningiomas, but the results were controversial. 7,8,27 In the present study, we found that angiographic vascularity of meningiomas correlated with FA but not with ADC. Whereas ADC measures the average changes of water diffusivity, FA quantifies the diffusion anisotropy.…”
Section: Discussioncontrasting
confidence: 45%
“…5 DSC-PWI, on the other hand, measures T2*-weighted signal intensity loss that occurs dynamically over bolus injection of contrast medium, from which relative CBV, a quantitative marker of tumor angiogenesis, can be computed. 6 Both DTI 7,8 and DSC-PWI [9][10][11] had been reported to be useful in subtyping meningiomas. The microvessel area of meningiomas determined by histopathology was found to correlate with relative CBV derived from DSC-PWI.…”
mentioning
confidence: 99%
“…FA and MD were calculated by using standard algorithms as described in previous studies. 14,15 Isotropic DWI was obtained by averaging the anisotropic DWI encoded in 20 different directions. By using the coregistration module integrated in the software nordicICE, T2-weighted isotropic DWI, MD, and FA images were coregistered to postcontrast MPRAGE on the basis of 3D nonrigid transformation and mutual information before all visual inspections and quantitative measurements.…”
Section: Image Postprocessingmentioning
confidence: 99%
“…Newer imaging techniques such as Diffusion-weighted (DWI), MR perfusion (MRP), Diffusion Tensor Imaging (DTI), and MR spectroscopy (MRS) have been investigated in smaller series with lesser success and conflicting results. [25][26][27][28][29][30][31]. Our study shows that the conventional MR imaging may be used to differentiate between benign and atypical/malignant meningiomas via grade 4/4 vascularity, but high grade vascularity is of lesser importance than previous history of CVA.…”
Section: Discussionmentioning
confidence: 96%